Proceso de cohesión social en dos poblaciones retornadas en el departamento de Antioquia (Colombia), Dabeiba y Nariño (2017)
ABSTRACT: Forced displacement has negative effects on people’s life, their families and community networks get broken, social and cultural ties are lost. This research analyzes two experiences of returning after being subjected to forced displacement, one in the municipality of Dabeiba and the other one in the municipality of Nariño, both located in Antioquia, Colombia. The objective of this research is to explore, from a psychosocial perspective, issues like social cohesion and community building. This work was done from a symbolic interactionism perspective, using focal groups and interviews. Thirteen in-depth interviews with community members were done. This study concludes that requires an interdisciplinary accompaniment, systematic and articulated work is needed in order to promote processes of social autonomy on the studied communities. Social spaces that allow collective work and leadership development are also needed.